Response to salinity of the submerged aquatic vegetation species \(Najas indica\) (Willd.) Cham - Dang, Xuan Thi Le; Phan Thi, Thuy Hang; Ton That, Phap; Hoang Cong, Tin; Luong Quang, Doc (Vietnam Journal of Marine Science and Technology, 2022)
Najas indica (Willd.) Cham is known as a freshwater species of submerged aquatic vegetation. However, this species is widely distributed in both freshwater and brackish environments. This study examined the survival, growth rate and morphological performance of N. indica collected from the Cau Hai lagoon (Thua Thien Hue) against different salinity treatments in a mesocosm experiment to determine the optimal salinity for the species. The results showed significant effects of different salinities on survival rates, growth, biomass, and the morphological characteristics of N. indica. The species could survive and continue growing at 0–15 ppt but died completely at 20 ppt and 25 ppt after the first week of the 8-week experiment. Leaf length tended to be shorter in higher salinity. Shoot length, the number of internodes and branches per shoot, biomass reached the highest values at 5 ppt and 10 ppt. These suggested that the optimal salinity of the N. indica was at a range of 5–10 ppt. Study results were informative to explain the distribution change of the freshwater originated hydrophyte N. indica in lagoon environments in Vietnam.